QoS ANALYSIS ON THE ICONNET NETWORK SINGKAWANG CITY - Pulungan, Annisa Kynamehule; Marpaung, Jannus; Imansyah, Fitri (Faculty of Engineering, Universitas Tanjungpura, 2023)
The purpose of this study is to analyze the Quality of Service (QoS) parameters on the Iconnet network by measuring throughput, packet loss, delay and jitter parameters when doing online games (mobile legend) and video calls (WhatsApp) with a bandwidth of 10 Mbps and 20 Mbps using wireshark application. This study discusses the causes of reduced QoS parameter values on networks in Singkawang City, data were taken at 3 times, namely morning, afternoon and evening. From all the recapitulation of QoS parameter measurement results, it can be concluded that the value of each QoS parameter can vary for each package which includes bad, good and very good categories even on the same Bandwidth package. The causes of high and low values of QoS parameters are different, Throughput is caused by the number of arrivals of packets measured during the observation process, Packet Loss is caused by the number of queues that exceed capacity, Delay is caused by the low Throughput value and the number of packets sent while the Jitter value is affected by the Delay value. External factors that can reduce the QoS value are weather conditions and the number of devices connected to the network. Network quality during the day and evening is the point when network traffic is very dense or traffic on the network is full (full traffic) where there are many users during these hours. The quality of data transfer speed is assessed with numbers 1 to 5, number 1 is the worst result, while number 5 is the best result. Packet Loss is caused by the number of queues that exceed capacity, Delay is caused by low Throughput values and the number of packets sent while the Jitter value is affected by the Delay value. External factors that can reduce the QoS value are weather conditions and the number of devices connected to the network. Network quality during the day and evening is the point when network traffic is very dense or traffic on the network is full (full traffic) where there are many users during these hours. The quality of data transfer speed is assessed with numbers 1 to 5, number 1 is the worst result, while number 5 is the best result. Packet Loss is caused by the number of queues that exceed capacity, Delay is caused by low Throughput values and the number of packets sent while the Jitter value is affected by the Delay value. External factors that can reduce the QoS value are weather conditions and the number of devices connected to the network. Network quality during the day and evening is the point when network traffic is very dense or traffic on the network is full (full traffic) where there are many users during these hours. The quality of data transfer speed is assessed with numbers 1 to 5, number 1 is the worst result, while number 5 is the best result. External factors that can reduce the QoS value are weather conditions and the number of devices connected to the network. Network quality during the day and evening is the point when network traffic is very dense or traffic on the network is full (full traffic) where there are many users during these hours. The quality of data transfer speed is assessed with numbers 1 to 5, number 1 is the worst result, while number 5 is the best result. External factors that can reduce the QoS value are weather conditions and the number of devices connected to the network. Network quality during the day and evening is the point when network traffic is very dense or traffic on the network is full (full traffic) where there are many users during these hours. The quality of data transfer speed is assessed with numbers 1 to 5, number 1 is the worst result, while number 5 is the best result.